2005
DOI: 10.1258/1357633053499831
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a digital store-and-forward colposcopic system - a pilot study to assess usability for telemedicine

Abstract: We evaluated the diagnostic reliability of cervical examination using digital colposcopy compared with conventional binocular colposcopy. A total of 315 patients were examined and diagnosed by a colposcopist on-site. During the colposcopic examination, digital camera images were stored on a PC (median five pictures per patient). A second physician, experienced in colposcopy, re-evaluated the initial diagnostic findings using the stored digital images. The primary and secondary findings in each patient were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Conversely, in a Botswanian study [ 19 ], the diagnostic concordance between nurse VIA and nurse photographic evaluation of VIA was 81%. Moderate agreement (kappa = 0.60) was also reported in a German study, where the primary and secondary examiners agreed in 69% of the cases [ 18 ]. Contrary to these studies, naked-eye visualization of the cervix instead of colposcopy was used in the present study, and this difference may have influenced the results.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Conversely, in a Botswanian study [ 19 ], the diagnostic concordance between nurse VIA and nurse photographic evaluation of VIA was 81%. Moderate agreement (kappa = 0.60) was also reported in a German study, where the primary and secondary examiners agreed in 69% of the cases [ 18 ]. Contrary to these studies, naked-eye visualization of the cervix instead of colposcopy was used in the present study, and this difference may have influenced the results.…”
Section: Discussionmentioning
confidence: 59%
“…Smartphones, with the ability to take high-quality images and to send information quickly, have a clear advantage over “standard” digital cameras: They are very easy to use, do not need an external light source and permit easy zooming in the photography as well as very quick and easy comparison of the different pictures taken (native, VIA and VILI). Experience has shown that smartphones have the capacity to monitor subtle cervical changes and to introduce a simple quality assurance process that can probably be easily integrated into a cervical cancer screening program [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that videocolposcopy can provide an accurate diagnosis, reduced travel distance and can enable training of healthcare staff. 25 Schadel et al 44 evaluated the use of digital colposcopy against conventional binocular colposcopy. 44 Three hundred and fifteen patients had a colposcopic assessment onsite and had their images saved which were reviewed by another colposcopist.…”
Section: Resultsmentioning
confidence: 99%
“… 25 Schadel et al 44 evaluated the use of digital colposcopy against conventional binocular colposcopy. 44 Three hundred and fifteen patients had a colposcopic assessment onsite and had their images saved which were reviewed by another colposcopist. There was agreement between the examiners in 69% of cases (k=0.60).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation